1995
DOI: 10.1300/j010v21n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Social Work in Pediatric Oncology:

Abstract: When a child is diagnosed with cancer, the family is confronted with meeting both the physical and psychosocial needs of the child and maintaining normal family functioning. This study assessed the perceived psychosocial needs of 77 families who have a child diagnosed with cancer. Preliminary results suggest practical application for social work interventions in specific areas such as the development of an informal support network, enhancement of communication within families concerning the disease, the need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 16 publications
1
24
0
3
Order By: Relevance
“…Similar to other studies of children with cancer [3,10], information was the greatest category of need among our population. This is in contrast to previous research that suggested that low-income families are likely to place informational needs on the backburner as they have practical needs that require more immediate attention [5].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to other studies of children with cancer [3,10], information was the greatest category of need among our population. This is in contrast to previous research that suggested that low-income families are likely to place informational needs on the backburner as they have practical needs that require more immediate attention [5].…”
Section: Discussionsupporting
confidence: 84%
“…The greatest needs cited among predominantly Caucasian families with a child with cancer have been reported to be informational, emotional, and financial [10]. In particular, these families need help communicating with friends and families about their child's cancer and they worry about the long-term emotional effects on both the children with cancer and their siblings [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These increases have had dramatic impact on many aspects of society, particularly on the caregiving by family members. For example, families of children with cancer have faced increased responsibilities in caring for the child's needs, whether physical, social, and/or psychological, in addition to caring for other family members during the diagnosis and treatment periods (Fletcher & Clarke, 2003;Overholser & Fritz, 1991;Shields et al, 1995). Additionally, one cannot overlook the impact on parents whose child does not survive after what is essentially a longterm illness.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Thus, parents describe the diagnosis and treatment of child with cancer as one of the most stressful times in their lives. [38,39,40,41,42,43] The spiritual beliefs possessed by the parents appeared to offer a great deal of comfort to them while dealing with their child's illness. Spirituality was described as being highly personal and extremely powerful in its own right [6].…”
Section: J Pediatr Oncol Nursmentioning
confidence: 99%